2000
DOI: 10.1590/s0100-84042000000400011
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the intercellular protuberances in leaves of Paepalanthus superbus Ruhl. (Eriocaulaceae)

Abstract: -(Ultrastructure of the intercellular protuberances in leaves of Paepalanthus superbus Ruhl. (Eriocaulaceae)). Mature leaves of Paepalanthus superbus exhibit intercellular protuberances between the inner periclinal walls of the epidermal and the parenchyma cells surface, as well as on the surface of the parenchyma mesophyll cells. These structures are mostly prominent around the parenchyma cells, forming a gel capsule-like structure. Histochemical tests with ruthenium red indicate the pectic nature of the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Protuberances then form after the rupture of these strands as parenchyma development proceeds. In contrast to this view, other authors stress the possibility that the pectic filaments observed in ferns (Potgieter and van, Wyk 1992;Carr and Carr, 1975) and other plant groups (Machado et al, 2000;Butterfield et al, 1981;Davies and Lewis, 1981) may be derived from new materials laid down after intercellular space formation. According to Veys et al (2002) protuberances appear both under stress conditions, such as wounding (Davies and Lewis, 1981) and grafting (e.g.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Protuberances then form after the rupture of these strands as parenchyma development proceeds. In contrast to this view, other authors stress the possibility that the pectic filaments observed in ferns (Potgieter and van, Wyk 1992;Carr and Carr, 1975) and other plant groups (Machado et al, 2000;Butterfield et al, 1981;Davies and Lewis, 1981) may be derived from new materials laid down after intercellular space formation. According to Veys et al (2002) protuberances appear both under stress conditions, such as wounding (Davies and Lewis, 1981) and grafting (e.g.…”
Section: Introductionmentioning
confidence: 94%
“…Subsequently, similar structures were found in the intercellular spaces of seeds, leaves, stems and roots of many monocotyledons, dicotyledons, ferns and fern allies (for a review see Potgieter and van Wyk, 1992). These have been referred to as intercellular wall thickenings (Luerssen, 1873), pectic strands (Carr and Carr, 1975;Carr et al, 1980a, b), pectic filaments (Carr and Carr, 1975;Potgieter and van Wyk, 1992), pectic warts (Kisser, 1928;Carlquist, 1956Carlquist, , 1957, scala (Potgieter and van Wyk, 1992), pectic projections (Davies and Lewis, 1981;Veys et al, 1999Veys et al, , 2000Veys et al, , 2002, microprojections (Rolleri, 1993), beads (Jeffree and Yeoman, 1983; Barnett and Weatherhead, 1988), bead-like projections (Miller and Barnett, 1993), papilla-like structures (Suske and Acker, 1989), protuberances (Donaldson and Singh, 1984), intercellular protuberances (Butterfield et al, 1981;Machado et al, 2000), and intercellular pectic protuberances (IPP) (Potgieter and van Wyk, 1992;Machado and Sajo, 1996;Rolleri, 2002;Mengascini, 2002;Prada and Rolleri, 2005;Rolleri and Prada, 2006). Besides Asplenium, protuberances in ferns and fern allies have been studied in Angiopteris (Carr and Carr, 1975;Rolleri, 2002;Mengascini, 2002), Pteridium (Carr and Carr, 1975), Pteris (Schenck, 1886), Blechnum (Schenck, 1886), Christensenia…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have explored water movement in the mesophyll, methodological limitations make it difficult to determine water routes within a leaf (Berry et al, 2019). Our results with the apoplastic tracer showed for the first time evidence of lateral water redistribution in the mesophyll through pectin-rich intercellular protuberances (Machado et al, 2000). These protuberances can function like bridges that interconnect the mesophyll cells, facilitating lateral redistribution of absorbed dew (Figure 4).…”
Section: Leaf Anatomy and Fwu Pathwaysmentioning
confidence: 79%